Intermuscular hydatid cyst in the thigh musculature: a case report - Aderaw Getie; Bahiru Atinafu; Misganaw Alemu; Genetu Belay; Dereje Bedane Hunde (Journal of Medical Case Reports)
Abstract Introduction Echinococcus granulosus, a tapeworm, is responsible for causing hydatid disease. Hydatid cysts rarely affect the musculoskeletal system, occurring in less than 5% of cases. This case report presents the clinical presentation, diagnosis, and management of muscle echinococcosis. Case presentation A 28-year-old Black African female presented with a 4-month history of left anteromedial thigh swelling. Despite mild burning pain, she remained functional. While pyomyositis was initially considered, ultrasound and magnetic resonance imaging suggested hydatid disease. Surgical excision was performed, and histopathology confirmed the diagnosis. The patient received albendazole and praziquantel for 4 and 2 weeks, respectively, as adjunctive therapy. A year-long follow-up revealed good progress and continued health. Conclusion Primary muscle hydatid cysts should be considered in the differential diagnosis of cystic, painless, localized masses in the muscular system, especially in endemic regions. Serological tests and imaging techniques are essential for investigation. Complete surgical excision and anthelminthic therapy should be pursued when possible.